Working-week flexibility: Implications for employment and productivity - Victoria Osune (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper evaluates the effects for the Spanish case of allowing greater flexibility regarding the weekly hours worked on the working week, employment and productivity. A baseline model economy is calibrated to reproduce the cross-sectional distribution of workweeks across plants, as well as certain features of the Spanish economy. The author compares the steady-state status quo, where a forty-hour workweek is imposed and no flexibility is allowed, and the steady-state of economies with a higher degree of flexibility in weekly hours. The 2012 reform is found to preserve employment and generate a 1.72% increase in productivity. In the work-sharing scenario, the increase in employment (1.86%) comes at the expense of a lower increase in productivity (1.31%). Finally, the full flexibility scenario preserves employment and generates a substantial increase in productivity (2.6%).
Keywords: E24; E60; J21; 330; FDI; Workweek; wages; employment; productivity